Gaya Kepemimpinan Religio Paternalistik: Analisis Buku “Persepsi Santri Terhadap Perilaku Kepemimpinan Kiai di Pondok Pesantren” karya Muhammad Nur Salim Asy’ari - Ummi Ulfatus Syahriyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
This article aims to analyze the implementation of the paternalistic religio leadership style contained in Muhammad Nur Salim Asy'ari's book entitled "Students' Perceptions of Kiai Leadership Behavior in Islamic Boarding Schools." Leadership style is the way a leader carries out his leadership function. The connotation of kiai leadership in pesantren is often branded as authoritarian and arbitrary. Even though the leadership of the kiai in pesantren is very closely related to religious values. Apart from that, pesantren life has its own cultural pattern, which eventually forms a kiai's leadership style. This study used library research methods with content analysis. Then check the validity of the data using source triangulation. Based on the BS Cheng theory, there are three indicators of paternalistic leadership: autocracy, benevolence, and morals. If an analysis is carried out on the book "Santri's Perceptions of Kiai Leadership Behavior in Islamic Boarding Schools," it is shown that; the autocratic aspect is shown by the kiai providing direction and guidance to the management; the aspect of virtue is shown by the attitude of syafaqah/affection; and the moral aspect is shown by the kiai always providing role models for santri, both in the form of aqwal and ahwal.